The Use of Augmented Reality Based-Learning Media to Reduce Students' Misconceptions - Frelyana Tiro; Afadil Afadil (Universitas Tadulako, 2022)
The research objective is to determine whether using AR molecules as a learning medium can assist students in reducing their misconceptions about molecular materials. It was pre-experimental research with a one-group pre-test-post-test design. The average level of validity of the learning media used, according to the findings, is 70.3% (